The Peroxisome Proliferator-Activated Receptor γ Agonist Pioglitazone Protects Vascular Endothelial Function in Hypercholesterolemic Rats by Inhibiting Myeloperoxidase - Dapeng Zhang; Yehong Wang; Ming Yi; Suli Zhang; Ye Wu (Cardiology Research and Practice)
Objective. Hypercholesterolemia- (HC-) induced endothelial dysfunction is the first step of atherogenesis, and the peroxisome proliferator-activated receptor γ (PPARγ) has been reported to attenuate atherosclerosis formation; however, the underlying mechanisms are not fully understood. The present study was designed to determine whether myeloperoxidase (MPO) mediates HC-induced endothelial dysfunction and the role of the PPARγ agonist pioglitazone (PIO) in attenuating endothelial dysfunction. Methods. Male Wistar rats were fed with normal or high cholesterol diets for 8 weeks. HC rats were randomized to receive dapsone (DDS, the MPO inhibitor) during the last 6 days or PIO for the remaining 4 weeks. Vascular endothelial function was determined by comparing vasorelaxation to ACh, an endothelium-dependent vasodilator, and SNP, an endothelium-independent vasodilator in vascular rings in vitro. The vascular MPO activity, NOx content, and cGMP level were measured by the MPO activity assay kit, NO assay kit, and cGMP RIA kit. Results. Compared with rats fed with normal diet, endothelium-dependent vasodilation, NOx content, and cGMP level were decreased, and MPO activity was increased in thoracic aortas of rats fed with HC diet. There was a negative correlation between vascular endothelial function, NOx content or cGMP level, and MPO activity. PIO obviously reduced the MPO activity, increased NOx content and cGMP level, and improved endothelium-dependent vasodilation function in HC rats, which was essentially the same as that seen with DDS. And, there was a negative correlation between vascular endothelial function, NOx content or cGMP level, and MPO activity in the HC group and the PIO intervention group. Conclusion. MPO might provoke vascular endothelial dysfunction in hypercholesterolemic rats by reducing the NO biological activity and impairing the NO/cGMP/cGK signaling pathway. PIO might inhibit vascular MPO activity and increase NO bioavailability with the net result of reversing endothelial dysfunction.